Barriers to cancer screening for people with disabilities: A literature review. Issue 1 (January 2015) - Merten, Julie Williams; Pomeranz, Jamie L.; King, Jessica L.; Moorhouse, Michael; Wynn, Richmond D.
Abstract: Background: Over 50 million Americans are currently living with some form of disability. Studies have shown that people with disabilities are underinsured, have less access to health care, and are more likely to engage in risky health behavior. Routine preventive screenings for breast, cervical and colorectal cancer are recommended for all adults to improve early detection and treatment of cancer. Although early detection of cancer offers the best chances for treatment and survival, cancer screening has been limited for many people with disabilities. Objective: To present results of a scoping review of studies focused on barriers to cancer screening for people with disabilities. Methods: Online databases were searched for research articles on barriers to cancer screening (breast, cervical, prostate, and colorectal) in people with disabilities. Results: Thirty-five peer-reviewed articles met inclusion criteria. Existing research on cancer screenings, particularly prostate cancer, among people with disabilities is limited. Current studies suggest that those with advanced disabilities are not being screened for cancer as often as the able-bodied population with the exception of military veterans. Education, income, age, employment, screening history, tobacco use, activity level, disability level, and geography affected screening rates. Conclusions: Barriers include cost, access, health care provider discomfort, and physical and cognitive restraints. Future interventions to improve routine preventive cancer screenings rates could include specialized health care provider training, community interventions, emphasis on the value of health promotion and the specific health care needs of people with disabilities.